Beyond win–win: A syncretic theory on corporate stakeholder engagement in sustainable development. (18th February 2019) - Martinez, Fabien; Peattie, Ken; Vazquez‐Brust, Diego
Abstract: This article explores the concept of syncretism to articulate the construct of a novel theoretical approach that may help to accelerate progress in developing substantively more sustainable business activities. One reason why the integration of environmental and social responsibility in business has been so difficult to achieve in practice is that it is not just a battle of competing business logics but a battle of faiths. The concept of syncretism, with its roots in religious synthesis, may be far more relevant and useful than conventional approaches to combining the two, which rarely seem to rise above a "win–win" appeal to logic. The connectionist logic of syncretism may show us a way beyond paradigmatic conformity in business sustainability research so that scholars with diverse theoretical backgrounds might have a common ground for discussion, find constructive connections, and engage in potentially more insightful and creative interactions to develop our understanding of corporate sustainability.